Implementation and Development of Qur’an Learning Method in Malaysia and Indonesia: An Analysis - Jaafar, Azhar; K, Munawir; Hamzah, Mohd Isa (Khalifa: Journal of Islamic Education, 2017)
The article aimed to analyze the implementation and development of Qur’an learning methods in two cognate countries namely Malaysia and Indonesia. The methodology used was content analysis, one of the research approaches in qualitative research. Data came from author’s reading of various theories, expert opinions and research results of previous researchers associated with education and learning of Qur’an. All data then collected, reduced, presented and closed with conclusions. At the beginning of the authors begin with the introduction, further discuss the urgency of learning and teaching of Qur’an, the method of learning Qur’an in the first period of Qur’an is revealed, the obligation to read Qur’an well and correctly, the description of methods and analysis of the implementation of learning Qur’an in Malaysia and Indonesia, factors that influence the success of learning Qur’an and conclude with conclusions. The results of the discussion of this article can at least be an additional reference material for Qur’an observers teachers Qur’an in particular, parents, community and the next researchers related to the study of Qur’an in Islamic education.